Periodontal tissue damage in smokers - Hutojo Djajakusuma (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
Dental plaque is the primary etiological factor in periodontal diseases. However, there are many factors that can modify how an individual periodontal tissue will respond to the accumulation of dental plaque. Among such risk factors, there is increasing evidence that smoking tobacco products alters the expression and rate of progression of periodontal diseases. The aim of this study was to find out the loss of periodontal tissue adhesion in smokers by measuring pocket depth using probe, and by measuring alveolar bone damage using Bone Loss Score (BLS) radiographic methods on teeth 12, 11, 21, 22, 32, 31, 41, 42. Based on T Test statistical analysis, there were significant differences in pocket depth damage of alveolar bone in smokers and non smokers. In conclusion there were increasing pocket depth and alveolar bone damage in smokers.